Serviceability performance of piled raft foundations under vertical loads in clayey and sandy soils - Der-Wen Chang; Shih-Hao Cheng; Wei-Cheng Zheng; Chan-Yen Tseng; Louis Ge (Soils and Foundations, 2025)
This study investigated the serviceability performance of piled raft foundations (or combined pile-raft foundations, CPRF) in various soils using three-dimensional (3D) finite element analysis. The piled raft foundation was assumed to be embedded respectively in homogeneous clayey soils and sandy soils under vertical loading. The displacements and reactions of the piles were carefully observed. In comparing the influences of soil stiffness, raft width, pile-to-pile spacing distance, and pile length, it was found that the embedment depth of the foundation could significantly affect the serviceability of the piles. For embedment depths ranging from 0 m to 12 m, the pile loads can be reduced by approximately 40 % to 60 % of the foundation load, depending on the number of piles involved. The displacements of piled raft foundations in clays decrease with increased embedment depth. However, the effects of embedment depth on foundation displacements are smaller in sands. Furthermore, the load ratio of the piles and the displacement ratio of the CPRF were calculated to demonstrate their dependence on the slenderness ratio of the piles and the number of piles. Both ratios aligned with the guidelines the International Society for Soil Mechanics and Geotechnical Engineering (ISSMGE) proposed for CPRF systems. Notably, attention is drawn to the depth of raft embedment, as it significantly influences pile responses.